A quasi-2D exploration of optimum design settings for geotextile-reinforced sand in assistance with PIV analysis of failure mechanism. Issue 3 (June 2023) - Ates, Bayram; Sadoglu, Erol
Abstract: Many earlier studies were focused on testing different types of geosynthetics to investigate effect of reinforcement on bearing capacity, but the effect of tensile strength on the failure mechanism has not been examined sufficiently. Within this scope, a test setup was prepared to apply strip loads on densely compacted reinforced sand under the plane strain condition. The tank containing the reinforced sand was a rectangular prism with perfect transparency, and its interior dimensions were 960 × 200 × 650 mm 3 . Firstly, optimum values of design variables (depth of first sheet, length and number of sheets, space between sheets, tensile strength of sheets) for the woven geotextile reinforced sand were determined experimentally. Then, the failure mechanisms of the soil, which were reinforced with geotextiles of different tensile strengths, were observed and analyzed with particle image velocimetry (PIV) technique. Consequently, the failure mechanism of the sand with a single geotextile reinforcement was similar to general shear failure of unreinforced soil. Contrarily, the failure surfaces were deeper and longer. Additionally, the deep-footing mechanism reached out large depth in the case of four reinforcement layers. The failure mechanism converted into a punching type due to a hypothetic increase in the bearing depth of reinforcement. Highlights: Failure mechanisms of reinforced soils with reinforcements of different tensile strengths were analyzed with PIV technique. The load-settlement and ultimate bearing capacity of strip footing on reinforced soil were studied. Bearing capacity factors and settlement reduction factors were determined from model test under plane strain condition. Effective depth can be found as 1.6 times the footing width under plane strain and load-controlled conditions. The optimum designing parameters for the strip footing model on reinforced sand were determined depending on footing width.